Teachers' code-switching in classroom instructions for low english proficient learners - Ahmad, Badrul Hisham; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Due to the alarming signals of declining proficiency level among English Language learners in Malaysia, this study set out to learn more about the learners’ perceptions of the teachers’ code-switching in English Language classrooms. The objectives of this study were to investigate a )learners’ perceptions of teachers’ code-switching, b)the relationship between teachers’ code-switching and learners’ affective support c) the relationship between teachers’ code-switching and learners’ learning success and d) the future use of code-switching in students’ learning. The study investigated 257 low English proficient learners attending Communication 1 proficiency course in a public university in Malaysia. A set of questionnaire containing 20 items using 5-points Likert-type scale was administered to measure the presence of code-switching in classrooms, the affective support and the learning success. The study proposed two hypotheses and the hypotheses were tested using Pearson product moment correlation analyses. The study found that learners perceived code-switching as a positive strategy due to the various functions it has. There are significant relationships between (1) teachers’ code-switching and learners’ affective support and (2) teachers’ code-switching and learners’ learning success. Learners also showed favourable support for future code-switching in the English classrooms. It is strongly believed that teachers’ code-switching is an effective teaching strategy when dealing with low English proficient learners.